INDONESIAN LOCAL FERMENTATION FUNCTIONAL FOOD DEVELOPMENT STRATEGY IN THE ERA OF PANDEMIC COVID 19 - Muchamad Bachtiar; Heny Herawati (Journal of Islamic, Social, Economics and Development, 2022)
Local fermented foods in Indonesia are highly diversed. It is commerciallyprospective to develope into higher value added products. Indonesian traditional custom foodregional-based has special characters to enter specific market segmentation, especially forlocal fermented food. Several processed and fermented products are tempeh, kefir, tauco, tape,nata de coco, bekasam, etc. The Covid 19 pandemic era has provided changes in marketsegmentation to start consuming functional foods that provide health benefits. Several bioactivecomponents and health benefits can be found in those local fermented foods. This situation alsoprovided a changes in the online marketing system-based that beneficial for those to access andshortens the supply chain, however, constrain of fermented product is their different â€œbesttimeâ€ to consume due to biological microbe mechanism. This issue need to solve byimplementing excellent strategy, a combination of fulfillment on demand side timely andexcellent quality product that affect by biological microbe mechanism. The strategy in ensuringproduct quality by controlling a several factors during processing and distribution so that thefunctional local fermented food products are still fit to consume and provide health benefits. Inthis paper, we examine important strategies for the development of local fermented functionalfood in Indonesia in the Covid 19 Pandemic Era.